Evaluation of Mycobacterium tuberculosis by conventional methods, GeneXpert and line probe assay in cases of extrapulmonary tuberculosis - Murhar, Renuka; Gajbhiye, Sunita; Zodpey, Sunanda Shrikhande; Lichade, Shailesh (International Journal of Research in Medical Sciences, 2023)
Background: Diagnosis of EPTB is often delayed due to its paucibacillary nature. Diagnostic modalities like conventional methods and molecular methods like GeneXpert are employed for Mycobacteria detection and their results are compared. Line Probe Assay is used for determination of resistance in first line and in second line anti-tubercular drugs. Methods: In this study 302 extrapulmonary samples from suspected cases of all age groups were included. Samples were first homogenised and decontaminated and then subjected to various diagnostic modalities like microscopy, culture and GeneXpert for Mycobacteria detection. Culture and smear positive isolates were subjected to LPA for determination of drug resistance in first and second-line anti-tubercular drugs. Results: Out of the 302 extrapulmonary samples, maximum samples were of lymph nodes (19.86%) followed by pus (17.88%). Male to female ratio was 1:3. GeneXpert detected 45.04% positive cases and 5.96% were rifampicin resistant. Positive samples detected by microscopy and culture were 21.19% and 24.17% respectively. When compared to culture, microscopy showed a sensitivity of 86.30% and specificity of 99.56%. GeneXpert reported 100% sensitivity and 72.48% specificity. LPA reported 9.45% isoniazid resistant cases, 4.05% rifampicin resistant cases and 5.40% both isoniazid and rifampicin resistant cases (MDR-TB). Out of the MDR-TB cases, 25% cases were resistant to fluoroquinolones indicating pre-XDR TB. Conclusions: For Mycobacterium tuberculosis detection in extrapulmonary samples, multiple modalities should be employed so that the bacilli in these samples is not missed and the turn-around time is lowered which is a key to TB control strategy.